2022
DOI: 10.1039/d1cc06786a
|View full text |Cite
|
Sign up to set email alerts
|

Reactivities of allenic and olefinic Michael acceptors towards phosphines

Abstract: Insights into the first step of R3P-catalysed Lu cycloadditions are given by the kinetics of phosphine additions to alkyl allenoates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To describe quantitatively the reactivity of electrophiles and nucleophiles, Mayr and co-workers proposed a three-parameter eq based on the electrophilicity E , solvent-dependent nucleophilicity N , and susceptibility s N : …”
Section: Resultsmentioning
confidence: 99%
“…To describe quantitatively the reactivity of electrophiles and nucleophiles, Mayr and co-workers proposed a three-parameter eq based on the electrophilicity E , solvent-dependent nucleophilicity N , and susceptibility s N : …”
Section: Resultsmentioning
confidence: 99%
“…11 In ongoing attempts to expand the use of compounds 1 to access novel chemical space by targeting highly functionalized enantioenriched heterocycles 2 via asymmetric -functionalization reactions, we now became interested in using allenoates 3 as possible C sp -electrophiles (undergoing -addition). [15][16][17][18][19] Interestingly, the acceptor properties of allenoates 3 can be tuned by nature of the catalyst system. 15 While the use of (chiral) phosphine catalysts usually allows for -additions, it has also been reported that the use of simple inorganic Brønsted bases, 17 chiral organobases, 19 or the use of chiral quaternary ammonium salt catalysts under classical phasetransfer conditions 18 allow for -selective additions of Cnucleophiles (i.e., in situ generated enolate species) with promising enantioselectivities.…”
Section: Paper Synthesismentioning
confidence: 99%
“…15 Lu and co-workers have used a catalytic amount of tertiary phosphine to undertake [3+2] cycloadditions of allene substrates, forming cyclopentene products. 16 More recently, this transformation has been studied in detail by Ofial and coworkers, with vinyl phosphonium intermediates being trapped to allow characterization of the phosphine addition products, 17 whose chemoselectivity is similar to that obtained from a hydrophosphination reaction.…”
Section: Introductionmentioning
confidence: 99%